Red blood cell concentrates treated with the amustaline (S‐303) pathogen reduction system and stored for 35 days retain post‐transfusion viability: results of a two‐centre study. Issue 3 (21st February 2017) - Cancelas, J. A.; Gottschall, J. L.; Rugg, N.; Graminske, S.; Schott, M. A.; North, A.; Huang, N.; Mufti, N.; Erickson, A.; Rico, S.; Corash, L.
Abstract : Background and Objectives: Pathogen reduction technology using amustaline (S‐303) was developed to reduce the risk of transfusion‐transmitted infection and adverse effects of residual leucocytes. In this study, the viability of red blood cells (RBCs) prepared with a second‐generation process and stored for 35 days was evaluated in two different blood centres. Materials and Methods: In a single‐blind, randomized, controlled, two‐period crossover study ( n = 42 healthy subjects), amustaline‐treated (Test) or Control RBCs were prepared in random sequence and stored for 35 days. On day 35, an aliquot of 51 Cr/ 99m Tc radiolabeled RBCs was transfused. In a subgroup of 26 evaluable subjects, 24‐h RBC post‐transfusion recovery, mean life span, median life span (T50 ) and life span area under the curve (AUC) were analysed. Results: The mean 24‐h post‐transfusion recovery of Test and Control RBCs was comparable (83·2 ± 5·2 and 84·9 ± 5·9%, respectively; P = 0·06) and consistent with the US Food and Drug Administration (FDA) criteria for acceptable RBC viability. There were differences in the T50 between Test and Control RBCs (33·5 and 39·7 days, respectively; P < 0·001), however, these were within published reference ranges of 28–35 days. The AUC (per cent surviving × days) for Test and Control RBCs was similar (22·6 and 23·1 per cent surviving cells × days, respectively; P > 0·05). Following infusion of Test RBCs, there were no clinically relevant abnormal laboratory values or adverse events. Conclusion: RBCs prepared using amustaline pathogen reduction meet the FDA criteria for post‐transfusion recovery and are metabolically and physiologically appropriate for transfusion following 35 days of storage.